Multiagent system technologies : 11th German Conference, MATES 2013, Koblenz, Germany, September 16-20, 2013. Proceedings - Thimm, Matthias; Paprzycki, Marcin; Klusch, Matthias (Lecture Notes in Computer Science, 2013)
This book constitutes the refereed proceedings of the 11th German Conference on Multiagent System Technologies, MATES 2013, held in Koblenz, Germany, in September 2013. The 29 revised full papers and 3 keynote talks presented were carefully reviewed and selected from various submissions. The papers cover a broad area of topics of interest ranging from issues of agent-based coordination to simulation to negotiation.